Magnetically separable core–shell iron oxide@nickel nanoparticles as high-performance recyclable catalysts for chemoselective reduction of nitroaromatics. Issue 1 (28th August 2014) - Rathore, Puran Singh; Patidar, Rajesh; Shripathi, T.; Thakore, Sonal
Abstract : A magnetically separable core–shell iron oxide@nickel nanocatalyst was synthesized, characterized and applied for the aromatic nitro group reduction. Abstract : A magnetically separable core–shell iron oxide@nickel (IO@Ni) nanocatalyst was synthesized by reduction of Ni 2+ ions in the presence of iron oxide (Fe 2+, Fe 3+ ) by a simple one-pot synthetic route using NaBH4 as a reducing agent and starch as a capping agent. The synthesized nanoparticles (NPs) were characterized by several techniques such as X-ray diffraction (XRD), high resolution transmission electron microscopy (HR-TEM), selected area electron diffraction (SAED), and energy dispersive X-ray spectroscopy (EDS). The core–shell iron oxide@nickel nanoparticles (IO@NiNPs) were found to have excellent activity for the hydrogenation reactions of aromatic nitro compounds under mild conditions using water as a green solvent. Excellent chemoselectivity and recyclability up to 30 cycles for the nitro group reduction was demonstrated.